2020
DOI: 10.1002/chem.201905740
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced and Heteromolecular Guest Encapsulation in Nonporous Crystals of a Perfluorinated Triketonato Dinuclear Copper Complex

Abstract: The flexible hostf ramework of ap erfluorinated mononuclear copper complex,[ Cu(L 1 ) 2 ]( 1,H L 1 = 3-hydroxy-1,3-bis(pentafluorophenyl)-2-propen-1-one), with aC uO 4 core reversibly encapsulateds everal organic guest molecules throughe lectrostatic interactions in its crystals. Hence, the correspondingd inuclearc omplex, [Cu 2 (L 2 ) 2 ]( 2,H 2 L 2 = 1,5-dihydroxy-1,5-bis(pentafluorophenyl)-1,4-pentadien-3-one), was prepared to enhanceg uest recognition and the ability to separate molecular mixtures. Complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 84 publications
0
5
0
Order By: Relevance
“…The Pt 2+ [10] and Pd 2+ [11] centers of square-planar metal complexes can act as halogen-bond acceptors upon their interaction with σh-donating organohalides, and the complexes are co-crystallized with πh-donating perfluoroaromatic species giving the sandwich structures based on π-hole• • • π interactions [12,13] when the nucleophile metal center and electron-poor molecule are opposite charge distributions [14]. We reported that the supramolecular association of square-planar Pt 2+ , Pd 2+ , and Cu 2+ β-diketonate complexes [15,16], which nucleophile characteristics of Pt 2+ and Pd 2+ are clearly shown in the results of their crystal packings in the solid state and DFT calculations. The axial surface on the Pt 2+ center in complexes shows high negative ESP and nucleophile that on Pd 2+ center remarkably changed the surrounding substitutions, e.g., the negative value for [Pd(dbm) 2 ] and neutral~positive for the corresponding perfluorinated complex, [Pd(L) 2 ] (L = bis(pentafluorobenzoyl)methanido − ), indicating the possibility of strict adjustment of the metal characteristics [15].…”
Section: Introductionmentioning
confidence: 99%
“…The Pt 2+ [10] and Pd 2+ [11] centers of square-planar metal complexes can act as halogen-bond acceptors upon their interaction with σh-donating organohalides, and the complexes are co-crystallized with πh-donating perfluoroaromatic species giving the sandwich structures based on π-hole• • • π interactions [12,13] when the nucleophile metal center and electron-poor molecule are opposite charge distributions [14]. We reported that the supramolecular association of square-planar Pt 2+ , Pd 2+ , and Cu 2+ β-diketonate complexes [15,16], which nucleophile characteristics of Pt 2+ and Pd 2+ are clearly shown in the results of their crystal packings in the solid state and DFT calculations. The axial surface on the Pt 2+ center in complexes shows high negative ESP and nucleophile that on Pd 2+ center remarkably changed the surrounding substitutions, e.g., the negative value for [Pd(dbm) 2 ] and neutral~positive for the corresponding perfluorinated complex, [Pd(L) 2 ] (L = bis(pentafluorobenzoyl)methanido − ), indicating the possibility of strict adjustment of the metal characteristics [15].…”
Section: Introductionmentioning
confidence: 99%
“…The intricate behavior of charges induced by fluorine not only determines the intrinsic properties of molecules but also their behavior in a plethora of chemical reactions and applications, from organic electronics to pharmaceuticals [7][8][9]. In the realm of our research, we have delved into the study of aromatic fluorine compounds [10][11][12][13][14], a category known for its significant impact on chemical compounds due to the electron-withdrawing nature imparted by the fluorine substitutions. Aromatic fluorine molecules, exemplified by entities such as pentafluorophenyl groups [1,[15][16][17], and heterocyclic molecules like those containing triazine rings [18] are distinguished as π-hole molecules [19][20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Intermolecular interactions involving hydrogen or p-block elements have been divided into two groups, based on the position of the region of electropositivity in the donating group . In a σ-hole (σh) donor, the electropositive site lies within the plane of the molecular framework, typically at the extension of a covalent bond; the electropositive region in π-hole (πh) donor lies perpendicular to the molecular plane. , A constantly growing part of recent reports is devoted to πh donors, which are involved in anion−π, , lone pair−π, and π–π interactions. These types of contacts are now widely utilized in crystal engineering, catalysis, materials science, and chemical and biological recognition. …”
Section: Introductionmentioning
confidence: 99%